Effective Factors Influencing on the Implementation of Knowledge Management in the Agricultural Bank of Qom Province - Mohammad Esmaiely; Mehrdad Niknam; Ali Badragheh (International Journal of Agricultural Management and Development, 2016)
The main objective of the present work was to study the factors affecting the deployment of knowledge management in Agriculture Bank of Qom Province. It was a causativerelational study in terms of data collection. Also, it was a field study, non-experimental in terms of variables control. Sample size was estimated by Morgan table and the data were collected by a questionnaire. The statistical population included manager, experts and assistants of Agriculture Bank in Qom Province including 250 people. Sample size was calculated (n = 152) by Morgan table. The reliability was estimated by a pretest with 20 questionnaires filled out by a statistical population similar the studied one. The validity was confirmed by experts whose advice was taken care of about modifying or replacing some questions. Finally, Cronbach's alpha was estimated for the questionnaire to be 0.81. To achieve research objectives, the descriptive statistics of frequency, mean, variance, and standard deviation and the inferential tests of correlation and multiple regressions were conducted by SPSS Statistical Software Package. Results revealed the significant relationship of knowledge management deployment with organization culture, knowledge sources, organization memory, and information technology at the one percent level with modified determination coefficient of 0.632. In other words, 63.2% of the variation of the dependent variable was accounted by independent variables (organization culture, knowledge sources, organization memory, and information technology).